The principle of constitutional equality and its implications on fundamental rights. Notes on articles 14 and 9.2 of the Spanish Constitution of 1978 - Páucar Espinoza, Margott (2008)
This study attempts to highlight the relationship between fundamental freedom and the Equality Principle. These concepts have evolved simultaneously as a result of certain ties that have united them since their origins - ties which have grown even stronger with the advent of the Welfare State and the concomitant notion of social rights. In such a system, equality is established as a condition of the exercise of human rights. To this end, the Spanish Constituent Assembly has included the various meanings of the Equality Principle in the Constitution in a holistic manner: formal equality in article 14 and material equality in article 9.2. lt has also included in article 14 a subsection referring to the non discrimination principle. This holislic character has been pointed out on several occasions by the doctrine of the Spanish Constitutional Court, as we shall see below.